Wild Olive Genotypes as a Valuable Source of Resistance to Defoliating Verticillium dahliae - Díaz-Rueda, Pablo; Aguado, Ana; Romero-Cuadrado, Laura; Capote, Nieves; Colmenero-Flores, José M. (Frontiers in Plant Science, 2021)
Resistance to the defoliating pathotype of Verticillium dahliae has been evaluated in a pool of 68 wild genotypes of olive belonging to the SILVOLIVE collection. Resistance was evaluated by assessing symptom severity using a 0–4 rating scale, estimating the relative area under the disease progress curve, determining the percentage of dead plants, and measuring the evolution of morphological parameters in inoculated plants over time. In addition, the density levels of V. dahliae at the stem of root-inoculated genotypes has been quantified by means of quantitative real-time PCR at 35 and 120 days after inoculation (dai). Fifteen genotypes (22%) were catalogued as resistant to V. dahliae (i.e. disease parameters did not significantly differ from those of the resistant cultivar Frantoio, or were even lower). Resistant genotypes are characterized by presenting a lower amount of V. dahliae DNA at 120 dai than at 35 dai, indicating their ability to control the disease and reduce the density of the pathogen. The rest of the evaluated genotypes showed variable levels of susceptibility. Overall analysis of all genotypes showed high correlation between symptomatology and the amount of V. dahliae DNA in the stem of inoculated genotypes at 120 dai, rather than at 35 dai. However, correlation at 120 dai was not observed in the set of resistant genotypes, suggesting that resistance to defoliating V. dahliae in olive is based on the occurrence of different resistance mechanisms such as avoidance or tolerance. These mechanisms are valuable for breeding programs and for the identification of target genes and resistant rootstocks to better control verticillium wilt in the olive tree.